An investigation of efficient muon production for use in muon catalyzed fusion - Spencer,Kelly R; Hart,LJF; Rose,SJ (Journal of Physics: Energy, 2021)
We model the energy cost of producing muons for use in muon catalyzed fusion and show that by careful design the cost can be reduced by a factor of 2.5 below current values. This is done by recapturing the kinetic energy of waste particles and generating heat through tritium breeding. When put together with the modeling of muon catalyzed fusion we estimate that electrical output/electrical input of 14% can be achieved currently.